Literature Review: Mathematical Creative Thinking Ability, and Students’ Self Regulated Learning to Use an Open Ended Approach - Ali, Damsir; Amir MZ, Zubaidah; Kusnadi, Kusnadi; Vebrianto, Rian (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
The ability to think creatively and self regulated learning is very important in learning mathematics, in order to train students to develop their creativity. But in reality, mathematics learning that is currently happening has not been able to develop mathematical creative thinking skills and increase students’ self-regulated learning. The purpose of this study is to examine the relationship between the open-ended approach and the ability to think creative mathematically and self-regulated learning and how to implement it in school in the perspective of literature review. The type of research used is literature review, where articles are collected using search engines such as EBSCO, Science direct, and Scopus. Based on the articles collected, the results show that: 1. Mathematics learning to use an open-ended approach has an effect on increasing students ‘creative thinking skills and self-regulated learning, 2. The open-ended approach is higher in increasing students’ creative thinking abilities compared to using a conventional approach, 3. The open-ended approach to learning has the following steps: a) the teacher organizes students in learning activities; b) the teacher exposes students to open problems; c) the teacher guides and directs students in solving problems with various solutions and various answers; d) students present their work and compare with the work of other students in front of the class; and e) students conclude the subject matter, which is guided by the teacher. 4. To apply open-ended learning, it is necessary to prepare learning that requires high creativity for a teacher.